Research on coal-bed image fractures identification based on fracture shape characteristics - LIU Yong; CUI Hongqing (Gong-kuang zidonghua, 2017)
In view of problems that existing coal-bed image fractures identification method does not take good account of shape characteristics of the fractures or overall information of the fractures is not well obtained, by analyzing coal-bed image and shape characteristics of the fractures in binary image under different gray thresholds, determination coefficient of the coal-bed fractures was defined, and regio's length, width and the ratio of length to width in the coal-bed binary image were defined as shape parameters. At the same time, a method of the coal-bed image fractures identification based on fracture shape characteristics was proposed. Under condition of the given shape parameters, travel a given gray scale threshold range and identify fracture regions in every coal-bed binary image, then merge all the identified fracture regions as the last coal-bed fractures identification result. Finally, an example was given to demonstrate effectiveness of the method. It is concluded that information of the coal-bed image fractures can be acquired to the maximum extent by traveling a certain gray scale threshold range and identify the coal-bed image fractures, and it can effectively improve accuracy of the coal-bed fracture identification by selecting reasonable thresholds of the shape parameters of the fracture determining coefficient.